(untitled) (Progress Annals: Journal of Progressive Research, 2025)
The article is devoted to a review of the history and culture of the Shiite communities of Central Asia, in particular Uzbekistan, which profess Shiism, from the Isnaasharid (Ismamite) and Ismaili interpretations. The historically proven centuries-old contradictions of Shiites and Sunnis sometimes took the form of not only confessional, political or diplomatic conflicts. They seriously influenced the mutual perceptions of Muslims of two confessional directions within Islam, which sometimes resulted in an almost physical hostility to Sunnis and Shiites. The hostility of these two confessional areas of Islam prompted their bearers to apply the label "wrong" in relation to each other. And sometimes it was difficult to separate simple confessional rejection from political confrontations, which, in turn, often became an occasion for mutual military expansion, bloody clashes, etc. Now, despite the prevailing predominantly Sunni-Hanafi religious environment, Shiites from time immemorial keep the features of religious ritual and their confessional self-identification. The article also discusses some historical data on the resettlement and penetration of Shiite currents in Central Asia.